2021
DOI: 10.1371/journal.pone.0249148
|View full text |Cite
|
Sign up to set email alerts
|

Ethnically biased microsatellites contribute to differential gene expression and glutathione metabolism in Africans and Europeans

Abstract: Approximately three percent of the human genome is occupied by microsatellites: a type of short tandem repeat (STR). Microsatellites have well established effects on (a) the genetic structure of diverse human populations and (b) expression of nearby genes. These lines of inquiry have uncovered 3,984 ethnically biased microsatellite loci (EBML) and 28,375 expression STRs (eSTRs), respectively. We hypothesize that a combination of EBML, eSTRs, and gene expression data (RNA-seq) can be used to show that microsate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Further, a genomic survey on STRs in human populations (Kinney et al, 2019 ) identified eSTRs whose frequencies significantly differ between ethnicities. The same group also found 15 eSTRs whose repeat length correlates with gene expression (Kinney et al, 2021 ).…”
Section: Phenotypic Diversity Created By Strs With...mentioning
confidence: 92%
“…Further, a genomic survey on STRs in human populations (Kinney et al, 2019 ) identified eSTRs whose frequencies significantly differ between ethnicities. The same group also found 15 eSTRs whose repeat length correlates with gene expression (Kinney et al, 2021 ).…”
Section: Phenotypic Diversity Created By Strs With...mentioning
confidence: 92%
“…Population information is mapped to the five super-populations (AFR, AMR, EAS, EUR and SAS) from the 1000 Genomes Project (1KGP) ( 39 ). The GTEx reference panel used by webTWAS consists mainly of individuals of European ancestry ( 40 , 41 ), and is not suitable for imputing GReX in non-European individuals due to variations in gene expression between different populations. We therefore only include GWAS statistics from the European super-population (EUR) in the current version of webTWAS.…”
Section: Methodsmentioning
confidence: 99%
“…Following this approach, nevertheless, it should be taken into account that SNPs might be characterized by weak or moderate phenotypic effects that cannot be reproduced in independent populations given their genetic heterogeneity in minor allele frequencies and linkage disequilibrium between the loci [ 85 , 86 ]. Importantly, some studies have recently reported genetic differences in glutathione metabolism between races or ethnicities [ 47 , 87 ].…”
Section: Discussionmentioning
confidence: 99%